Hubungan Self Efficacy Terhadap Kualitas Hidup Pasien Kanker Payudara - Supaati Supaati; Anis Ardiyanti; Nafisatun Nisa (Lembaga Pengembangan Kinerja Dosen, 2024)
Breast cancer is a cancer with a high mortality rate that primarily affects women. This disease can affect self-efficacy and quality of life. This study aims to determine the relationship between self-efficacy and the quality of life of breast cancer patients at SMC Telogorejo Hospital. This is quantitative research with a correlational approach. The purposive sampling technique was used in this study to sample 42 respondents. The study's results showed that most of the people who responded were between the ages of 46 and 55 (50.0%), had at least a high school diploma (47.6%), worked as housekeepers (47.6%), were married (90.5%), and had been through chemotherapy at least six times. Of those people, 39 (92.9%) had high self-efficacy and 36 (85.7%) had good quality of life. The Spearman test rank showed that there is no relationship between self-efficacy and quality of life in breast cancer patients (p-value = 0.077). Future researchers should consider expanding the scope of their research to enhance its quality by developing, adding variables, and conducting thorough analyses.